The factors influencing the practices of elite camogie managers - Connors, Philip; Earls, Des; Browne, Declan; Rankin, Paula (Scientific Journal of Sport and Performance, 2025)
Management in sport involves multiple responsibilities, including player management, stakeholder communication, and integrating technical, tactical, and physical preparation. While coaching practices, beliefs and barriers have been reported across sports, no research has examined the factors influencing elite camogie managers’ practices. This investigation aimed to redress that gap. Six senior camogie managers participated in semi-structured interviews focused on session planning, player monitoring, and other emergent topics. A six-step thematic analysis was used to analyse the data. Three key themes emerged: Barriers impacting player preparation, coaching beliefs, and managers’ sport science knowledge. Managers reported funding and resource availability as significant constraints on player development and monitoring. Managers described using a traditional coaching approach, with fitness and skills developed in isolation before game-based activities, with their sport science knowledge impacting their practices. Ensuring best practice in camogie should be a priority, with greater funding and sport science integration required at the elite level.